Modelling water resources for planning irrigation development in drought-prone southern Chile. Issue 5 (3rd September 2021) - McNamara, Ian; Nauditt, Alexandra; Zambrano-Bigiarini, Mauricio; Ribbe, Lars; Hann, Hamish
ABSTRACT: To foster poverty reduction in drought-prone Araucanía, the Chilean Irrigation Commission is planning an important expansion of irrigated areas. Scenarios incorporating climate change (2030–2059) were simulated for a pilot basin using the WEAP water allocation model, showing that larger irrigated areas, coupled with higher temperatures and less precipitation, are likely to cause severe seasonal water scarcity. As decision support for the planning of effective measures to increase drought resilience, we modelled the construction of two upstream reservoirs combined with higher irrigation efficiency. We find that unmet water demand can be reduced by up to 97.7% by these measures.